Ecobrick: A Solution for plastic Waste to Establish Zero Waste Village in Pamekasan Regency - Sufiyanto, Mohammad Imam; Handoko, Lukman; Mulyani, Sri; Ummah, Faizatul (Indonesian Journal of Community Services Cel, 2022)
The Covid-19 pandemic that is continuing to spread around the world has shifted and changed people lifestyle. On the other hand, waste volume is increasing because many people massively throw garbage into water sources or rivers which results in water and soil pollution. This research applied descriptive qualitative method with demonstration techniques. The residents were taught to make Ecobrick for reducing the amount of plastic waste. Ecobrick is very effective in empowering the community to cope with the increasing amount of inorganic waste. Ecobrick can increase the creativity and productivity of the community especially in terms of transforming inorganic waste to goods with economic value. The results indicated that the amount of plastic waste which was previously thrown to the rivers could be reduced by implementing Ecobrick program. This program reflected community innovation and creativity in utilizing unused items at home. At the end, Bunder village can be a zero-waste area and makes goods economical and valuable to be used by all society elements.